Pengaruh pergantian kurikulum merdeka terhadap hasil belajar siswa sekolah di Indonesia - Anggraeni, Tarisa Nurul (Maliki Interdisciplinary Journal, 2024)
In order to achieve education, a curriculum is needed as teaching material and maintain the effectiveness of the teaching and learning process in schools. Education Minister Nadiem Makarim initiated a new curriculum, namely the "independent learning curriculum" which has been used starting in 2022. This curriculum reaps many pros and cons regarding the effect of this curriculum change on student learning outcomes. This study aims to analyze and collect data on the relationship between the change of independent curriculum and the learning outcomes of school students in Indonesia. For this reason, further understanding is needed to deepen insight into these activities. Researchers use qualitative methods, namely techniques for collecting data based on previous research and online reference sources by taking keywords on the importance of student learning outcomes, the Merdeka curriculum, and the influence of curriculum changes as online reference sources.